2000
DOI: 10.1097/00003643-200001000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Alkalinization of amide local anaesthetics by addition of 1% sodium bicarbonate solution

Abstract: for this group of local anaesthetics. This study demonstrates that 1 mL of 1% sodium bicarbonate solution A number of methods exist by which the pH of local may be used to alkalinize this range of local anaesthetic solutions may be increased. Most comanaesthetics without the risk of precipitation. We also monly, these require the addition of differing amounts conclude that Ropivacaine (at concentration 0.75% of sodium bicarbonate solution according to the local and 1.0%), is unsuitable for alkalinization since… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 9 publications
4
23
0
Order By: Relevance
“…In the present study, we confirmed that LA solutions containing epinephrine were more acidic than their plain counterparts, consistent with previous reports (3,5,18). In addition to the lower initial pH, various additives, such as sodium metabisulphite and pH adjusters such as hydrochloric acid and sodium hydroxide contribute buffering capacity (16,18).…”
Section: Epinephrine-containing La Solutionssupporting
confidence: 93%
See 3 more Smart Citations
“…In the present study, we confirmed that LA solutions containing epinephrine were more acidic than their plain counterparts, consistent with previous reports (3,5,18). In addition to the lower initial pH, various additives, such as sodium metabisulphite and pH adjusters such as hydrochloric acid and sodium hydroxide contribute buffering capacity (16,18).…”
Section: Epinephrine-containing La Solutionssupporting
confidence: 93%
“…Hence, raising the pH closer to pKa increases the fraction of the drug in the nonionized form, increasing the proportion of the administered dose that can enter neurons. This hastens anesthesia onset, reduces pain transmission and, thus, lowers pain perception on LA infiltration into tissues (3,5,8,15,18). Alkalinization also increases intracellular concentration of carbon dioxide, which effectively decreases intracellular pH.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In one such study, Milner et al stated that 0.75% and 1% ropivacaine in 1% sodium bicarbonate established precipitation. 15 Since we added 8.4% sodium bicarbonate to the syringe at the precise moment of the procedure, we observed no significant precipitation. Studies regarding alkalinization in lower extremity blocks are very rare.…”
Section: Figurementioning
confidence: 75%